2018
DOI: 10.1002/jcp.27857
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone‐related peptide (1–34) promotes tooth eruption and inhibits osteogenesis of dental follicle cells during tooth development

Abstract: Dental follicle cells (DFCs) activate and recruit osteoclasts for tooth development and tooth eruption, whereas DFCs themselves differentiate into osteoblasts to form alveolar bone surrounding tooth roots through the interaction with Hertwig's epithelial root sheath (HERS). Also during tooth development, parathyroid hormone‐related peptide (PTHrP) is expressed surrounding the tooth germ. Thus, we aimed to investigate the effect of PTHrP (1–34) on bone resorption and osteogenesis of DFCs in vitro and in vivo. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 53 publications
1
22
1
Order By: Relevance
“…According to Wong et al (2019), PTHrP is an osteolytic and osteoblastic factor, which is widely expressed in bone metastasis of prostate cancer [30]. Its expression is present from birth, showing that the functional formation of the dental arch depends directly on the expression of PTHrP in the role of mediator of the autocrine system responsible for bone modeling and remodeling [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…According to Wong et al (2019), PTHrP is an osteolytic and osteoblastic factor, which is widely expressed in bone metastasis of prostate cancer [30]. Its expression is present from birth, showing that the functional formation of the dental arch depends directly on the expression of PTHrP in the role of mediator of the autocrine system responsible for bone modeling and remodeling [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Presently, most studies have focused on the characteristic and osteogenic differentiation of DFCs in different kinds of diseases, such as cleidocranial dysplasia, 28 30 which is the failure of tooth eruption associated with parathyroid hormone-related peptide. 31 However, no studies have compared DFCs between patients with DD-I and healthy individuals. Thus, to gain a better understanding of this disease, we explored the relationship between a VPS4B mutation and the osteogenesis mineralization abilities of DFCs.…”
Section: Discussionmentioning
confidence: 99%
“…27 Recent studies have focused on the characteristic and osteogenic differentiation of DFCs for all kinds of diseases, one such example being cleidocranial dysplasia, 28 30 which is failure of tooth eruption associated with a parathyroid hormone-related peptide. 31 However, thus far, no data exist on the potential functional roles that DFCs may have during root development in DD-I. DFCs can be obtained from impacted third molars 32 , 33 and have been shown to possess the capability of osteogenic differentiation in vitro when induced with the appropriate osteogenic medium.…”
Section: Introductionmentioning
confidence: 99%
“…DFCs on the root surface robustly expressed parathyroid hormone-related peptide (PTHrP) during tooth root formation and after tooth eruption, and PTHrP + DFCs differentiated into PDLCs, alveolar cryptal bone osteoblasts, and cementoblasts in acellular cementum [5, 49]. However, a previous study reported that PTHrP inhibited alveolar bone formation by suppressing WNT/ β -catenin signaling in DFCs, exhibiting upregulated RANKL/OPG ratio which was in favor of osteoclastogenesis [50, 51]. PTHrP + DFCs subgroups also expressed the PTHrP receptor (PPR) plentifully.…”
Section: Dfcs In Tooth Developmentmentioning
confidence: 99%